SUPPLY CHAINS ANALYSIS OF CHOOSING SUPPLIER IN RESTAURANT (CASE STUDY : NEW HONGKONG RESTAURANT) - Ferry Setianto; Jeremy Kenny; Liem Gai Sin (AIBPM Publisher, 2018)
A good quality of product does come from a good supplier. That what makes Supplier's quality is paramount for every company. This research is conducted to find the best way for choosing supplier for our company. We believe our research can be successfull due to the fact that there is only few of research here in Indonesia that concern about the importance of choosing the right supplier for the enterprise. We use New hongkong Restaurant as our case study with interview method as our way to collect the data as well as secondary data which will be collected from supplier and company that we choose. The data itself will be analyzed qualitatively in order to determind the right supplier for the enterprise. Keywords: Supplier, Retail Management, New Hongkong Restaurant, descriptive qualitative